Business Policies in the Competition of Micro,sSmall and mMedium enterprises in the production sector in Indonesia - Muh. Rizal S; Arismunandar; Rifdan (Technium Social Sciences Journal, 2023)
Business policy is a decision or action taken by an individual or group in an attempt to a specific goal that focuses on a business area without involving the government in decision-making. The purpose of this study is to examine how Indonesian small, medium, and microbusinesses compete with one another in the production sector. A qualitative approach to the idea of literature was adopted as the study methodology. Observations, interviews, and documentation are utilized as data collecting methods. The results of the research are to develop UMKM’s efforts to succeed in competition, among others: creating product innovations, developing product marketing, using digital marketing in developing markets and developing the digital economy. The Indonesian government has also initiated policies to enable entrepreneurs to run and develop sustainable business through government programmes such as infrastructure assurance, enterprise capital assistance and developing coordination with other enterprise partners. With the policy of the program, the Indonesian government must have a goal as an effective solution to the problems that business operators often face, especially in the legality of business permits, financing as well as the ability of the entrepreneur in producing business and conducting marketing business based on digitalization.